Protein requirements in larvae and adults of Scaptotrigona postica (Hymenoptera: Apidia, Meliponinae): Midgut proteolytic activity and pollen digestion - Do Carmo Zerbo, Aparecida [UNESP]; Lúcia, Regina [UNESP]; Silva de Moraes, M. [UNESP]; Brochetto-Braga, M. Regina [UNESP] (Elsevier, 2001)
The number and degree of digestion of pollen grains in the midgut and rectum, the midgut proteolytic activity and the time of pollen grain passage through the digestive tract in the stingless bee Scaptotrigona postica (Latreille) have been analyzed. The results show similar protein requirements among larvae, nurse bees and queens, as well as between forager bees and old males, but these requirements are higher in individuals from the former groups than in those from the latter. Although protein requirements have been demonstrated to vary according to a bee's activity in the colony, they are similar among bees from different castes or sexes. These changes in feeding behavior are related to the bee's function and to less competition for nourishment among individuals of the colony. It is also noted that pollen grains took between 6 and 28 h to pass through the digestive tract. Pollen grains are irregularly accumulated in the various regions of the midgut, which may reflect functional differentiation throughout the midgut. © 2001 Elsevier B.V.
Keywords: Adults; Larvae; Midgut; Pollen; Proteolytic activity; Stingless bee; protein; age; aged; animal tissue; bee; competition; controlled study; digestive system; embryo; feeding behavior; female; larva; male; midgut; nonhuman; pollen; priority journal; protein degradation; sex difference; social class; Animals; Bees; Digestion; Digestive System; Female; Male; Sex Factors; Time Factors